2006
DOI: 10.4141/s06-010
|View full text |Cite
|
Sign up to set email alerts
|

Soil nutrient stratification and uptake by wheat after seven years of conventional and zero tillage in the Northern Grain belt of Canada

Abstract: Soil nutrient stratification and uptake by wheat after seven years of conventional and zero tillage in the Northern Grain belt of Canada. Can. J. Soil Sci. 86: 767-778. The distribution of NaHCO 3 -extractable nitrate-N, ammonium-N, phosphorus (P) and potassium (K) with soil depth (0 to 20 cm in 5-cm increments) at Fort Vermilion (58°23′N 116°02′W), Alberta, was described in the 7th and 8th years of conventional and zero tillage following placement of red clover (Trifolium pratense) green manure (GM), field pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 28 publications
4
27
0
Order By: Relevance
“…Previous studies conducted in Canada reported that fertilized NT had a greater soil mineral N and extractable P in the top 5 cm layer and to some extent down to 10 cm, and a depletion of N and P in sublayers; however, soil mineral N and extractable P uniformly distributed down to 20 cm under moldboard plow (MP) (Lupwayi et al 2006;Cade-Menun et al 2010;Messiga et al 2012). These findings indicated that soil depth at 0-5 cm under NT can be the most active layer for potential N and P losses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies conducted in Canada reported that fertilized NT had a greater soil mineral N and extractable P in the top 5 cm layer and to some extent down to 10 cm, and a depletion of N and P in sublayers; however, soil mineral N and extractable P uniformly distributed down to 20 cm under moldboard plow (MP) (Lupwayi et al 2006;Cade-Menun et al 2010;Messiga et al 2012). These findings indicated that soil depth at 0-5 cm under NT can be the most active layer for potential N and P losses.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural practices, including tillage, fertilization, and crop rotation, could affect the transformation and movement of soil N and P. Studies have shown that notill (NT) management has caused the stratification of soil organic carbon (Zibilske et al 2002), nitrate (Grant and Lafond 1994;Lupwayi et al 2006), and extractable P (Cade-Menun et al 2010;Messiga et al 2012;Abdi et al 2014). Previous studies conducted in Canada reported that fertilized NT had a greater soil mineral N and extractable P in the top 5 cm layer and to some extent down to 10 cm, and a depletion of N and P in sublayers; however, soil mineral N and extractable P uniformly distributed down to 20 cm under moldboard plow (MP) (Lupwayi et al 2006;Cade-Menun et al 2010;Messiga et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This gradient of P concentration is due in part to year-to-year broadcast or band application of P fertilizer at or near the same sowing row, to the absence of mixing of P fertilizers with soil and crop residues left on the soil surface after harvest, and to the subsequent leaching of P from crop residues (Duiker and Beegle, 2006). Phosphorus stratification has implications for crop nutrition, since P depletion in the rooting zone, where P is needed by plant roots, may reduce crop yield (Lupwayi et al, 2006). Several strategies have been suggested to address this issue, including strategic tillage (Dang et al, 2015) and the collection of separate soil samples from different layers to capture the vertical variability found in the rooting zone and thus ensure better fertilizer P recommendations and placement methods (Cade-Menun et al, 2010).…”
mentioning
confidence: 99%
“…Previous research under long-term no-tillage (NT) management has shown higher amounts of available P in the surface thin layer (0 to 5 cm or less) under NT than CT (Eckert 1985;Weil et al, 1988;Karlen, 1991;Ismail et al, 1994;Selles et al, 1997;Selles et al, 1999;Lupwayi et al, 2006, Mathers & Nash, 2009, Cade-Menun et al, 2010. Similarly, in our study, the amounts of extractable P in the surface 0-7.5 cm soil layer were greater under NT compared to RT, but the amounts of extractable P in the 7.5-15 and 15-20 cm layers were greater with RT compared to NT.…”
Section: Discussionmentioning
confidence: 99%